INVENTARIZATION OF CORAL REEFS IN THE WATERS OF RAKATA ISLAND, KRAKATAU ISLANDS - M Husien Ferdiansyah; Endang Linirin Widiastuti; Teguh Ismail; Gregorius Nugroho Susanto (AQUASAINS, 2019)
Abstrak Indonesia is an ideal place for coral growth because of the tropical climate. Rakata Island is included in the Krakatau Islands Nature Reserve and Marine Reserve area which is influenced by the volcanic activity of son of Krakatau Archipelago and human activities. Both of these activities will affect the growth of coral reefs. The purpose of this study was to determine the current condition of coral reefs and the diversity of living coral forms on Rakata Island. Collecting data for analysis of coral reef cover using the Line Intercept Transect (LIT) method was parallel to the coastline of Rakata Island at two points. The percentage of live coral cover from points I and II at a depth of 5 meters was 50.69% and 33.80% classified as in good and moderate conditions respectively. While the percentage of live coral cover at a depth of 10 meters at points I and II were 41.90 % and 16.01% whice were in moderate and poor conditions. The coral reefs mostly found in point I were leaf corals (CF) namely Turbinaria reniformis and Turbinaria frondens, while in point II were massive corals (CM) were found i.e. Goniastrea edwardsi, Favia pallida, Montastrea valenciennesi, Favites abdita, Astreopora listeria, and Favites complanata.